"'It is a safe space': self-harm self-help groups". Issue 1 (12th March 2018) - Boyce, Melanie; Munn-Giddings, Carol; Secker, Jenny
Abstract : Purpose: The purpose of this paper is to present a qualitative analysis of the role of self-harm self-help groups from the perspective of group members. Design/methodology/approach: A qualitative case study approach guided the research, which involved working with two self-harm self-help groups and all regularly attending members. Findings: A thematic approach to the analysis of the findings indicates that self-harm self-help groups can provide a safe, non-judgemental space where those who self-harm can meet, listen and talk to others who share similar experiences for reciprocal peer support. Offering a different approach to that experienced in statutory services, the groups reduced members' isolation and offered opportunities for learning and findings ways to lessen and better manage their self-harm. Research limitations/implications: This was a small-scale qualitative study, hence it is not possible to generalise the findings to all self-harm self-help groups. Practical implications: The value of peers supporting one another, as a means of aiding recovery and improving well-being, has gained credence in recent years, but remains limited for those who self-harm. The findings from this research highlight the value of self-help groups in providing opportunities for peer support and the facilitative role practitioners can play in the development of self-harm self-help groups. Originality/value: Self-harm self-help groups remain an underexplored area, despite such groups being identified as a valuable source of support by its members. This research provides empirical evidence, at an individual and group level, into the unique role of self-harm self-help groups.